Dark money : the hidden history of the billionaires behind the rise of the radical right - Mayer, Jane (Doubleday, 2017)
Why is America living in an age of profound economic inequality? Why, despite the desperate need to address climate change, have even modest environmental efforts been defeated again and again? Why have protections for employees been decimated? Why do hedge-fund billionaires pay a far lower tax rate than middle-class workers? --Publisher.